2017
DOI: 10.1002/cctc.201601518
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary Amines as Ligands in a Four‐Step Tandem Reaction of Hydroformylation and Hydrogenation: An Alternative Route to Industrial Diol Monomers

Abstract: With the reactions ystem [Rh(octanoate) 2 ] 2 and triethylamine, diols are produced in ah igh yields of up to 79 %w ith full conversion of intermediate aldehyde and no evidence of olefin hydrogenation. The scopeo ft he reaction was evaluated and the optimised reaction conditions were successfully scaled up to a2 Lr eactor.F inally,t he Rh/amine catalystc omplex was recycled by asimple water extraction of the diol-product.Scheme1.Industrialapproach from dcpd 1 to TCD-diol 6 vs. new route.[a] S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…According to the findings of previous investigations,, bidentate ligands only shift the formation towards aldehydes (Table , entry 1.4 & entry 1.5), meaning no active rhodium hydrogenation species is formed without an amine. These investigations showed that only rhodium and triethylamine produced high yields of TCD‐diol 6 , indicating a crucial limitation for the further application of this pathway in a tandem reaction sequence.…”
Section: Investigation Of the Hydrohydroxymethylationsupporting
confidence: 51%
See 4 more Smart Citations
“…According to the findings of previous investigations,, bidentate ligands only shift the formation towards aldehydes (Table , entry 1.4 & entry 1.5), meaning no active rhodium hydrogenation species is formed without an amine. These investigations showed that only rhodium and triethylamine produced high yields of TCD‐diol 6 , indicating a crucial limitation for the further application of this pathway in a tandem reaction sequence.…”
Section: Investigation Of the Hydrohydroxymethylationsupporting
confidence: 51%
“…As reported recently by the authors, a high yield of 79 % TCD‐diol 6 was obtained in toluene and Et 3 N (entry 1.1) . If tert ‐amyl alcohol, a solvent that is widely used for direct catalytic amination reaction, was used, the activity was inhibited, leading to a TCD‐diol 6 yield of only 21 % (Table , entry 1.2).…”
Section: Investigation Of the Hydrohydroxymethylationmentioning
confidence: 56%
See 3 more Smart Citations